The Implementation of Inheritance Based on The Tribe of Kaili Ledo and Islamic Inheritance Laws - Luawo, Fipy Rizky Amalia; Amalia, Haswida (Jurnal Dinamika Hukum, 2019)
Law is an inherent part of Indonesian society, which does not only national law but also customary law. One of the customary laws in Indonesia is the Kaili customary law. Kaili customary law is only applicable to specific communities. Whereas Islamic law applies broadly to all Muslims. One of them is in the field of inheritance law. From many disputes that occur in inheritance law, the distribution of heritage in inheritance law has always been a major problem that occurs in society, both in Kaili's customary inheritance and Islamic inheritance laws. It is interesting to find out more that each of the rules has different dispute resolution where Kailiâ€˜s customary inheritance law trusts Totua nu ada as a person who has the capability to distribute the heritage. This study was conducted by the Conceptual and Comparative Approach. In conclusion, Kaili indigenous community, are familiar with customary institutions, and, in Islamic law, they have the Religious Courts to resolve their inheritance disputes.Â Keywords: Customary Inheritance law, Islamic Law, Division of inheritance